Dysregulated miRNA biogenesis downstream of cellular stress and ALS‐causing mutations: a new mechanism for ALS. (1st September 2015) - Emde, Anna; Eitan, Chen; Liou, Lee‐Loung; Libby, Ryan T; Rivkin, Natali; Magen, Iddo; Reichenstein, Irit; Oppenheim, Hagar; Eilam, Raya; Silvestroni, Aurelio; Alajajian, Betty; Ben‐Dov, Iddo Z; et al.
Abstract: Interest in RNA dysfunction in amyotrophic lateral sclerosis (ALS) recently aroused upon discovering causative mutations in RNA‐binding protein genes. Here, we show that extensive down‐regulation of miRNA levels is a common molecular denominator for multiple forms of human ALS. We further demonstrate that pathogenic ALS‐causing mutations are sufficient to inhibit miRNA biogenesis at the Dicing step. Abnormalities of the stress response are involved in the pathogenesis of neurodegeneration, including ALS. Accordingly, we describe a novel mechanism for modulating microRNA biogenesis under stress, involving stress granule formation and re‐organization of DICER and AGO2 protein interactions with their partners. In line with this observation, enhancing DICER activity by a small molecule, enoxacin, is beneficial for neuromuscular function in two independent ALS mouse models. Characterizing miRNA biogenesis downstream of the stress response ties seemingly disparate pathways in neurodegeneration and further suggests that DICER and miRNAs affect neuronal integrity and are possible therapeutic targets. Synopsis: Amyotrophic Lateral Sclerosis‐causing mutations affect DICER complex activity and lead to altered miRNA biogenesis. Reduction in miRNA levels unifies genetically unrelated forms of human ALS. miRNA biogenesis is attenuated by cellular stress or by ALS proteins, TDP‐43, FUS or SOD1. Stress granule protein interactions with DICER complex underlie reduced activity. Enoxacin, a DICER agonist, mitigates miRNA biogenesis defect and neuromuscular deterioration in models of ALS. Abstract : Amyotrophic Lateral Sclerosis‐causing mutations affect DICER complex activity and lead to altered miRNA biogenesis.